Pengaplikasian Elektronik dalam penghasilan Karya Seni Kinetik - Mohd Fauzi, Bin Abdul Manab (Universiti Malaysia Sarawak (UNIMAS), 2007)
This project involved experiment toword electronic component that can be applied on circuit board to produce kinetic energy. Electronic component such as capasitor, transistor and other electronic component usually used on the circuit board. The purpose that using the electronic component are to make sure how electronic component can be used to produce kinetic energy. An artwork has been produce due to experimentation on electronic circuit of robot that move through kinetic energy.